Study the effects of bromothymol blue material on the optical properties for polystyrene (PS). (Baghdad Science Journal, 2013)
Films of pure polystyrene (ps) and doped by bromothymol blue material with percentages(4%) prepared by using casting technique in room temperature , the absorption and transmission spectra has been recorded in the wavelength rang (200-900)nm and calculated refractive index , reflectivity, real and imaginary parts of dielectric constant and extinction coefficient . this study has been done by recording the absorption and transmission spectra by using spectrophotometer .